Monitoring and evaluation of projects and programs (Journal of Economic Research & Business Administration, 2015)
In the transition to a program budget format of no small importance are issues of control over the implementation of programs, as well as questions assessing the efficiency and effectiveness of their implementation. In this regard, in the article the approach control, result oriented and its most substantial aspects – the processes of monitoring and evaluation of projects and programs. The paper also identifies the main criteria for evaluating the programs, shows the chain of the project results, the relationship of the evaluation criteria and the development goals of the program, disclosure of stages of the cycle of monitoring and evaluation of the results
Keywords: Management for results; monitoring of the project; evaluation of the project and program; effectiveness of the project